The Influence of Agility Training on Basketball Dribble Ability at Universitas PGRI Palembang Basketball KOP - Bayu Buana Pratama; Rury Rizhardi; Husni Fahritsani (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
The purpose of this study was to determine whether there was an effect of agility training on the ability to dribble basketball at KOP basketball at the University of PGRI Palembang. The research method used is a quantitative research method. The number of population and samples used in this study were 20 people. The results showed that agility training could improve dribbling in KOP basketball athletes at PGRI Palembang University because there was an increase after being given treatment compared to before being given treatment